Redox-driven formation of hausmannite-type manganese oxide and its catalytic performance - Awaluddin, Amir; Ilahi, Aulia Nur; Fachran Putra Deraf, Ivano; Siregar, Siti Saidah; Saputra, Edy (Faculty of Engineering Universitas Riau and Applied Materials and Technology Society, 2025)
Various manganese oxides have been reported to be an active catalyst for degradation of a dye. The synthetic manganese oxides can be conducted by several methods with the products having the different physicochemical properties and structures. This research focused on the synthesis of hausmanite-type manganese oxide (Mn2O3) by hydrothermal method with different mole ratio of KMnO4/glucose (3:1 and 2:3) and its application as a Fenton catalyst for the degradation of methylene blue (MB). The as-synthesized manganese oxides were then characterized by XRD for their structure and crystallinity and FTIR and Raman spectroscopy for the lattice vibrations. The average oxide state (AOS) of manganese in the as-synthesized manganese oxide was determined by the back titration method. The XRD results indicated the presence of mixed phases with hausmanite phase as major component and cryptomelane and birnessite phases as minor ones. FTIR spectroscopy results showed the presence of O-Mn vibrations at wavelengths of 468 cm-1, 487cm-1, and 726 cm-1. In addition, Raman spectroscopy results clearly showed the specific vibrations of hausmanite at 655 cm-1 and 653 cm-1, respectively. The low value of Mn AOS was obtained when the oxide was prepared in low ratio KMnO4/glucose and short reaction time. The as-synthesized hausmanite was tested as the Fenton catalyt for the degradation of MB. The as-synthesized hausmanite synthesized with different mole rasio and reaction time showed similar catalytic activity for the degradation of MB with the highest MB degradation of 90.76%